2012
DOI: 10.1093/hmg/dds088
|View full text |Cite
|
Sign up to set email alerts
|

Human and mouse ZFY genes produce a conserved testis-specific transcript encoding a zinc finger protein with a short acidic domain and modified transactivation potential

Abstract: Mammalian ZFY genes are located on the Y chromosome, and code putative transcription factors with 12–13 zinc fingers preceded by a large acidic (activating) domain. In mice, there are two genes, Zfy1 and Zfy2, which are expressed mainly in the testis. Their transcription increases in germ cells as they enter meiosis, both are silenced by meiotic sex chromosome inactivation (MSCI) during pachytene, and Zfy2 is strongly reactivated later in spermatids. Recently, we have shown that mouse Zfy2, but not Zfy1, is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Recently we have shown that in the adult testis this transcription is limited to germ cells, starting in leptotene spermatocytes, with more robust transcription in zygotene spermatocytes, followed by silencing in pachytene spermatocytes as a consequence MSCI; there was no resumption of transcription prior to MI, but transcription was shown to have resumed in (Y-bearing) round spermatids [7]. However, no data are available for interphasic secondary spermatocytes [14].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently we have shown that in the adult testis this transcription is limited to germ cells, starting in leptotene spermatocytes, with more robust transcription in zygotene spermatocytes, followed by silencing in pachytene spermatocytes as a consequence MSCI; there was no resumption of transcription prior to MI, but transcription was shown to have resumed in (Y-bearing) round spermatids [7]. However, no data are available for interphasic secondary spermatocytes [14].…”
Section: Resultsmentioning
confidence: 97%
“…Zfy1 and Zfy2 have the same predicted DNA target sequences, so if both are robustly expressed during zygotene, why is the apoptotic role limited to Zfy2 ? A plausible explanation is provided by our finding that during the pre-pachytene phase of transcription, alternative splicing of Zfy transcripts leads to ∼81% of Zfy1 transcripts lacking exon 6 with the encoded protein lacking transactivation (TA) activity, whereas ∼96% of Zfy2 transcripts have exon 6 and thus a functional TA domain [7]. Our current TA domain analysis further demonstrates that the few full length Zfy1 transcripts that are produced during zygotene generate a protein with a much less potent TA domain than that of Zfy2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitation by qRT-PCR of Zfy1 transcripts with and without exon 6 from Zfy1 hi and Zfy1 lo transgenic ovaries was as described previously (Decarpentrie et al, 2012), with 7-week-old XX ovary and 15 dpp XY testis as negative and positive controls, respectively. All qRT-PCR reactions were carried out in triplicate per assay.…”
Section: Methodsmentioning
confidence: 99%
“…Here we recall two of these genes, for the sake of completeness ( Figure 2). Zinc finger protein, Y-linked (ZFY) is expressed in germline, and Leydig cells [139], and mice knockout for Zfy genes are infertile [140]; in addition, its function in somatic cells seems minor, if any [141]. Nonetheless, the lack of known mutations of this gene alone in infertile men does not allow confirming what it does in human spermatogenesis.…”
Section: Spermatogenesis-related Genes In the Ypmentioning
confidence: 99%